2005
DOI: 10.1029/2004gl022271
|View full text |Cite
|
Sign up to set email alerts
|

A reconstructed Siberian High index since A.D. 1599 from Eurasian and North American tree rings

Abstract: The long‐term variability of the Siberian High, the dominant Northern Hemisphere anticyclone during winter, is largely unknown. To investigate how this feature varied prior to the instrumental record, we present a reconstruction of a Dec–Feb Siberian High (SH) index based on Eurasian and North American tree rings. Spanning 1599–1980, it provides information on SH variability over the past four centuries. A decline in the instrumental SH index since the late 1970s, related to Eurasian warming, is the most strik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 25 publications
(59 reference statements)
7
64
0
Order By: Relevance
“…Spectral analyses indicate significant (α = 0.05) peaks at 11.6 year, 7.1 year and 3.3 year in the Jungar, and at 21.8 year and 6.3 year in the Trans-Ili ring variance. The spectral peaks are in agreement with significant modes of variability seen in winter atmospheric oscillations such as the Siberian High index (SH), East Asian Winter Monsoon (EAWM) and Arctic Oscillation [34][35][36]. Figure S1.…”
Section: Apple Growth Variationssupporting
confidence: 61%
See 1 more Smart Citation
“…Spectral analyses indicate significant (α = 0.05) peaks at 11.6 year, 7.1 year and 3.3 year in the Jungar, and at 21.8 year and 6.3 year in the Trans-Ili ring variance. The spectral peaks are in agreement with significant modes of variability seen in winter atmospheric oscillations such as the Siberian High index (SH), East Asian Winter Monsoon (EAWM) and Arctic Oscillation [34][35][36]. Figure S1.…”
Section: Apple Growth Variationssupporting
confidence: 61%
“…Both composite chronologies show considerable annual variation in apple growth and longer-period variance changes frequency in the late 1970s ( Figure 5 [34][35][36]. (Table S1) calculated with single linkage of Ward minimum variance method.…”
Section: Apple Growth Variationsmentioning
confidence: 99%
“…During this period, other large-scale circulation phenomena such as the Siberian High (reconstructed by Meeker and Mayewski, 2002) might have gained more importance in the study area. Although the Siberian High has been observed to extert a large influence on air temperatures especially in Asia (Gong and Ho, 2002) and the Pacific (D'Arrigo et al, 2005), also eastern parts of Europe are under the influence of this anticyclonic field (Katsoulis et al, 1998). de Jong et al (2013b), for example, found evidence of strong influence of the Siberian High on central Alpine winter temperatures during the LIA, implying that the influence of the Siberian winter anticyclone extended over Central Europe as far as the eastern Swiss Alps.…”
Section: Factors Controlling Winter Severitymentioning
confidence: 95%
“…The Siberian high or anticyclone is a quasi-stationary and semipermanent feature of the climate system, with major implications for the climate of Eurasia (D'Arrigo et al 2005;Panagiotopoulos et al 2005), particularly the monsoon systems of the region. It is most dominant during the boreal winter.…”
Section: E Initial Evaluations Of Other Climatic Features In Hadslp2mentioning
confidence: 99%